FORMALIZING INFORMAL ECONOMY: IMPROVING DECENT WORK AND TAX COLLECTION IN OIC MEMBER COUNTRIES - Bukhari M. S. Sillah (Journal of Islamic, Social, Economics and Development, 2019)
Informal economy is pervasive in OIC Member Countries (MCs) measuring on average 30 percent of GDP and 80 percent of employment. Beside unaccounted economic output, informal economy is costing on average 4.15 percent of GDP in tax losses, which is higher than average government health expenditure of 2.3 percent of GDP and average government education expenditure of 4.12 percent of GDP in OIC MCs. Informal economy obscures unemployment rate. Countries with high informal economy have low unemployment rates, but they are generally working in poverty and they are far less productive than workers in the formal economy. Overregulation and complicated government business processes can cause enterprises to go informal. On the other hand, because of asymmetry of information, poorly endowed producers go informal to avoid inefficient government services and to incubate informally. Assuming informal economy is perfectly competitive, and its production function follows a Cobb-Douglas format, then its long-run labor demand will be a function of selling price, labor wage, and quantity produced. this labor demand function is expanded to include regulatory burden and e-government and private property rights to measure asymmetry of information. E-government applications, which are held to simplify government processes and increase transparency, are found to be negatively associated with informal economy. One percent increase in e-government utilization was found to be associated with a decline of informal labor demand ranging from 0.001 percent to 3.4 percent. While, 1 percent increase in regulatory burden is associated with 2 percent increase in quantity of informal labor demanded. Therefore, formalizing informal economy requires simplifying regulatory framework and high utilization of e-government applications. While poorly endowed enterprises, which often incubate informally need proper incentives to grow and transition them into formal economy.